The Application Of The Principle Of Notary Prudence In Knowing The Applicant By Notary - Gerin Prayoga; Jawade Hafidz (Jurnal Akta, 2019)
Abstract. The purpose of this study was to: 1) To Know and analyze the application of the principle of notary prudence In Knowing the applicant. 2) To Detect and Analyze Effects Of Authentic And Notary Deed Not Applying the Precautionary Principle  In Knowing the applicant. The data used in this study are primary data, secondary data and data that can support tertiary study, which was then analyzed by the method of description and interpretation.Based on the results of data analysis concluded that: 1) The principle of recognizing User Services as referred to in paragraph (1) at least includes identification of User Services, User Verification Transaction Monitoring Services and User Services. Reporting to the Financial Transaction Analysis and Reporting Center (PPATK) is recommended if it is believed their suspicions of money laundering schemes will be carried out, the registration obligation remains to be done, the registration once for serving. Reporting through the application system GRIPS (Gatahering Report Information Processing System). 2) an authentic deed which turned out later proven to be pecucian money, then it becomes the responsibility of the applicant own. Notaries who do not register GRIPS, will apply sanctions in the form of the temporary closure of access to AHU account on line, and thus access to the system notary Legal Administration (SABH) will be automatically blocked.Keywords: Notary; Precautionary Principle; Protection.